1998
DOI: 10.1109/75.661135
|View full text |Cite
|
Sign up to set email alerts
|

Linear high-efficiency microwave power amplifiers using bandpass delta-sigma modulators

Abstract: A novel amplifier configuration is described, in which a bandpass delta-sigma modulator is used to produce a two-level (digital) signal representing an analog radio frequency (RF) input. Subsequently, a switching-mode amplifier and bandpass filter are used to amplify the signal and remove unwanted spectral components. This configuration has the potential of achieving high efficiency (typical of switching mode amplifiers) together with high linearity. A simulated implementation with GaAs heterojunction bipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…The signal's adjacent channel power ratio stayed well below the UMTS spectrum mask, allowing for some non-linearity from a subsequent PA. Direct modulation was also proposed by Jayaraman et al (1998), utilizing a bandpass ΣΔ modulator, simulated with GaAs HBT technology. Discussions on efficiency were presented, and it was indicated that the linearity demands were moved from the PA to the ΣΔM.…”
Section: Direct Rf Modulationmentioning
confidence: 99%
“…The signal's adjacent channel power ratio stayed well below the UMTS spectrum mask, allowing for some non-linearity from a subsequent PA. Direct modulation was also proposed by Jayaraman et al (1998), utilizing a bandpass ΣΔ modulator, simulated with GaAs HBT technology. Discussions on efficiency were presented, and it was indicated that the linearity demands were moved from the PA to the ΣΔM.…”
Section: Direct Rf Modulationmentioning
confidence: 99%
“…The approach of using these different parts in an emitter was first presented by A. Jayaraman and al. [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Publication of work on class S power amplification has increased with interest in finding suitable means of integrating the baseband DSP and RF front end functions of wireless devices. Class S PA theory is detailed in many sources including [2] and [3], results of simulations for devices operated in current mode and voltage mode at high frequency are shown in [4] and [5] respectively. Experimental measurements for a complete design at RF frequencies are not as widely available.…”
Section: Introductionmentioning
confidence: 99%